Endometrial cancer with implantation metastasis to vagina: a case report - Sapiee, Muhammad Eimaduddin; Wan Abas, Wan Rosmidah; Ramli, Roziana; Mohd Yusof, Muhd Afif; Nasaruddin, Ahmad Fazlin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Authors present a case of vaginal implantation metastasis following a diagnosis of endometrial cancer. A 58-year-old lady presented with postmenopausal bleeding and was later diagnosed to have endometrial cancer. She underwent an extra-fascial hysterectomy and bilateral salpingo-oophrorectomy with pelvic lymphadenectomy for Stage 3A endometrioid adenocarcinoma of the endometrium. The lymph nodes and cervix were free from the disease and no lymphovascular invasion was seen on the pathological specimen. She defaulted adjuvant radiotherapy and was lost to follow up. Six months later she had a tumour recurrence at the vaginal introitus just below the urethral orifice and awal from the vaginal vault with similar histopathological findings as previous cancer. This case highlights the rare occurrence of implantation metastasis of endometrial cancer.